If you are familiar with the exponential function bN = M, then you should know its logarithmic equivalence which is logbM = N. These two seemingly different equations are in fact the same or equivalent in every way. Look at their relationship using the definition below.
Definition of a Logarithmic Function
Let b a positive number but b ≠1. We say logb M = N (read as, log of base b of M is N) is defined as…
logbM = N ⇔ bN = M
*the symbol ⇔ means equivalent or the same
The purpose of the equivalent equations, as shown above, is to provide a direct link between logarithmic form and exponential form. Understanding this basic concept can help us solve some algebra problems that require switching from one form to another.
Let’s examine further how the variables M, N and b are rearranged when the logarithmic form is expressed as exponential form, vice versa.
Observations of the “switch” in positions of the variables:
- The subscript b in log form becomes the base in exponential form.
- The base N in log form becomes the exponent or superscript of b in exponential form.
- The variable M is isolated on one side of the equation.
Here are a few quick illustrations on how this logarithmic and exponential equivalence are applied.
1) log381 = 4
2) log232 = 5
3) log5125 = 3
4) log7 49 = 2
5) log8 512 = 3
6) log10 100 = 2
7) log10 1,000 = 3
8) log10 10,000 = 4
9) log64 2 = 1/6
10) log81 3 = 1/4
Since 34 = 81
Since 25 = 32
Since 53 = 125
Since 72 = 49
Since 83 = 512
Since 102 = 100
Since 103 = 1,000
Since 104 = 10,000
Since 641/6 = (26)1/6 = 2
Since 811/4 = (34)1/4 = 3
Now we are going to discuss “special cases” that naturally arise from the basic definition of logarithm in terms of exponential equation. We will use the definition above in order to answer some of these questions. The best way to point out the concept is through the use of examples.
Examples of How to Solve Basic Logarithmic Equations
Example 1: Solve for y in logarithmic equation log33 = y.
Rewriting the logarithmic equation log33 = y into exponential form we get 3 = 3y. What do you think is the value of y that can make the exponential equation true? In other words, we want to find the exponent in which 3 be raised in order to get 3. It looks like the only answer is 1 because when y = 1 we have 3 = 31.
In fact, we can generalize this idea into a simple rule…
The logarithm of a number wherein the base is the number itself is ALWAYS equal to 1.
Example 2: Solve for x in logarithmic equation log81 = x.
This logarithmic equation in exponential form is written as 1 = 8x. What could possibly be the value of the exponent x in order to make it a true statement? Using the Zero Property of exponent, b0 = 1, we know that any number (exception of zero), when raised to zero, is always equal to 1. It makes perfect sense that in 1 = 8x, the value must be x = 0 because 80= 1 .
There’s also a rule that handles such case when we attempt to get the logarithm of 1 with any base.
The logarithm of 1 with any values of b ( b is a positive number but b ≠1) is ALWAYS equal to 0.
Example 3: Solve for k in logarithmic equation log4(−1) = k.
Transforming into exponential equation, we have −1 = 4k. This is like a “trick” question, right? We need to find the exponent k to make the exponential equation a true statement.
Is there really such value? I don’t think there is one! In fact, we can’t find any number that we can raise 4 by to give −1. Therefore we say that there’s no solution, or undefined.
The logarithm of a negative number is undefined.
Example 4: Solve for w in logarithmic equation log2(0) = w.
The last “special case” happens when we try to find the logarithm of zero. Converting that log equation again into exponential we obtain 0 = 2w. We are faced again by an odd situation because we want to raise the base 2 by some exponent so that it results to zero. Is there such value? You can try. But you should agree that no such value exists! Therefore, this is another case where our answer is undefined or no solution.
The logarithm of zero is undefined.